Transisi demografi dan cabaran pembangunan lestari di Pulau Tuba, Langkawi - Mustaffa Omar,; Ishak Yussof, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
This paper discusses three of the following: (i) the demographic transition as experienced in Pulau Tuba, Langkawi (ii) development challenges due to underway demographic transition, and (iii) recommend appropriate measures and strategies for development in accordance with demographic trends in the study area. The main purpose of this article is to evaluate the impact of Langkawi’s development on the demographic transition in Pulau Tuba. The small island ecosystems conceptual framework has been chosen to guide the discussion. Data for this study is gathered through questionnaire using census method in May-June 2005. Our study revealed that changes in the ecosystem of the Langkawi Island for nearly two decades ago resemble the ecosystems of other Malaysian states on the mainland. However, our analysis also shows that the economic and infrastructure development in Langkawi, which concentrated mainly in Kuah, produced limited trickle down effects to the people livelihood in the surrounding small islands such as Pulau Tuba. The study shows that the Pulau Tuba ecosystem conditions which were characterised by a small population and less dense; lack in physical, financial and human capital investments; limited social and economic network that led many failed to seize the opportunities made available to them. The situation is made more difficult when the small islanders and their local leaders lack the autonomy and freedom to bring economic and social development directly in Pulau Tuba without the approval of the central administration. This led the residents of this small island continuously being marginalized from the mainstream of development